Innovation of Hydrocarbon Investigation Using Audio-Magnetotelluric in Cepu Field, Indonesia - Aditama, Iqbal Fauzi; Widodo, Widodo (Makara Journal of Technology, 2017)
An audio-magnetotelluric (AMT) survey has been performed at Cepu oil field located in Indonesia. The objective of this research is to detect resistivity structures of this important hydrocarbon rock. This research can be classified as an innovation in application of the AMT method for hydrocarbon exploration. The lack of seismic resolution has been provided by the AMT method, especially in the location of sub-basalt and sub-salt plays. In additional, the cost of AMT survey is quite low compared to seismic. The forward modelling is included in this research to understand the measurement data response from a mathematical model. In the field campaign, AMT data were acquired along two profiles in a frequency range of 0.1 to 8000 Hz. Anticlinal structure that has an E-W trend has also been identified by AMT resistivity model. Analyses of the AMT data suggest signatures of hydrocarbon reservoir from the anticlinal structure that indicated by a low resistivity zone. The basement structure is estimated to be located at 1600 m or deeper. This study concludes that, as far as the hydrocarbon prospects are concerned, the AMT results seem to confirm the continuation of the anticlinal structure, which was identified as the primary hydrocarbon prospect in previous studies.